QUANTITATIVE TOOLS OF MONETARY POLICY AND IMPACT ON DETERMINING THE IRAQI DINAR EXCHANGE RATE (World Economics and Finance Bulletin, 2023)
The importance of the study is in identifying the monetary policy tools, whether traditional ones or new tools, that were used in Iraq by the Central Bank after 2003, namely (currency auction, existing facilities), as the study confirmed that the use of quantitative and new tools by the bank The Central Bank was able to achieve its main objectives, achieving stability in the general level of prices, and controlling the rampant inflation, as the inflation rate decreased from 5.33% in 2003 to 9.1% in 2013, and this led to achieving relative stability in the general level of prices, and then determining stability. In exchange rates, the model was formulated based on economic theory, as the legal reserve, open market operations, and discount rate were identified as explanatory variables for the adopted variable, the exchange rate. The test results showed that there is co-integration and a long-term equilibrium relationship between the monetary policy variables and the exchange rate rate. It was found that there is only one causal relationship in one direction between the legal reserve and the exchange rate .